Specificity protein 1-induced serine peptidase inhibitor, Kunitz Type 1 antisense RNA1 regulates colorectal cancer cell proliferation, migration, invasion and apoptosis through targeting heparin binding growth factor via sponging microRNA-214. Issue 2 (1st February 2022) - Fang, Ying; Yang, Qianqian
ABSTRACT: Previous studies indicated that long noncoding RNA (lncRNA) serine peptidase inhibitor, Kunitz type 1 antisense RNA1 (SPINT1-AS1) could function as an oncogenic gene in various human cancers. However, the regulatory mechanisms of SPINT1-AS1 in the tumorigenesis of colorectal cancer (CRC) remain unclear. It was found that SPINT1-AS1 was upregulated in CRC and contributed to the poor prognosis of CRC patients. Silencing of SPINT1-AS1 inhibited proliferation and metastasis but increased apoptosis of CRC cells. Furthermore, we found that SP1 could activate SPINT1-AS1 by acting as a transcription factor. Meanwhile, we identified miR-214 was negatively regulated by SPINT1-AS1. Furthermore, miR-214 repression restored the suppressive effects on malignant biological behaviors of CRC caused by SPINT1-AS1 silencing. In addition, SPINT1-AS1 mediated HDGF expression through targeting miR-214. Finally, overexpressed heparin-binding growth factor (HDGF) overturned the effects on viability, metastasis, and apoptosis of CRC cells induced by SPINT1-AS1 depletion or miR-214 upregulation. In conclusion, our results demonstrated that SP1-induced SPINT1-AS1 could facilitate CRC progression by inhibiting miR-214 and increasing HDGF expression. These findings might provide a new approach for CRC treatment.